ANALYSIS OF SERVICE QUALITY AND PRICE ON PRODUCTS PURCHASE DECISIONS AT CITIMART GUNUNGSTOLI - Epianus Lahagu; Yuterlin Zalukhu; Edward Harefa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The quality of service and product prices offered by retail businesses will greatly affect the ability to compete in an effort to dominate the market. The purpose of this research is to examine the effect of service quality and product price on customer satisfaction simultaneously and partially at Citimart Gunungsitoli. This research is a quantitative correlational research method. The sample in this study was 67 customers at Citimart Gunungsitoli. Methods of data collection using interviews and questionnaires. Data analysis was performed by multiple linear regression analysis. The results obtained in the study indicate that service quality and customer value have a significant effect on customer satisfaction, and product prices have a positive and significant effect on customer satisfaction at Citimart Gunungsitoli. These findings provide consideration for Citimart Gunungsitoli in preparing the best strategy to be able to retain customers and their presence in the retail business competition.